Pengaruh promosi online dan persepsi harga terhadap keputusan pembelian pada Thrift Galery Kemuning di Bangkalan - Solehartatik, Novia; Mada, Yudhi Prasetya (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
Based on existing phenomena and problems, this study aims to determine the effect of online promotions and price perceptions on purchasing decisions at Thrift Gallery Kemuning Bangkalan. The method used in this research is quantitative. The subjects in this study were consumers of Thrift Galery Kemuning Bangkalan with a sample of 97 respondents, then the data collection tool in this study was a questionnaire. The results of this study indicate that there is an influence between online promotions and price perceptions on purchasing decisions at Thrift Gallery Kemuning Bangkalan, either partially or simultaneously. The result of the coefficient of determination is 0.958, which means that 95.8% of the Buying Decisions are influenced by Online Promotion (X1) and Price Evaluation (X2). While the remaining 4.2% is the influence of other variables outside the variables studied in this research.